2023
DOI: 10.3390/agronomy13030643
|View full text |Cite
|
Sign up to set email alerts
|

Application of Synthetic Consortia for Improvement of Soil Fertility, Pollution Remediation, and Agricultural Productivity: A Review

Abstract: Climate change, inadequate possessions, and land degradation all pose obstacles to modern agriculture. In the current scenario, the agriculture industry is mainly dependent on the use of chemical-based pesticides and fertilizers that impact soil health and crop productivity. Moreover, water scarcity leads farmers in drastically affected regions to use heavy metal-enriched water sources mainly originating from industrial sources for field crops irrigation. Soil pollutants can be carried into the human body via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(28 citation statements)
references
References 178 publications
1
27
0
Order By: Relevance
“…Moreover, in consortia, cells have higher adaptability and viability in relation to environmental factors (pH, temperature, concentration of pollutants, etc.) [ 119 ]. Despite this, most artificial microbial consortia face problems of non-sustainable functioning [ 120 ].…”
Section: Analysis Of Current Trends In the Development Of Fungal-cont...mentioning
confidence: 99%
“…Moreover, in consortia, cells have higher adaptability and viability in relation to environmental factors (pH, temperature, concentration of pollutants, etc.) [ 119 ]. Despite this, most artificial microbial consortia face problems of non-sustainable functioning [ 120 ].…”
Section: Analysis Of Current Trends In the Development Of Fungal-cont...mentioning
confidence: 99%
“…These findings imply that waxy sorghum intercropped with soybean can increase enzymes activities and thus improve the quality of waxy sorghum rhizosphere soil. Soil microbes are an important part of soil ecosystem, and their community composition and quantity changes reflect soil quality and health to a certain extent, and are also the key factors to overcome continuous cropping obstacles [50,51]. Previous researches showed that rhizosphere soil microbes of crops were significantly affected by intercropping [33,43,52].…”
Section: Plos Onementioning
confidence: 99%
“…For instance, PGP microbes promote biological nitrogen fixation, phosphate solubilization, production of phytohormones, and biocontrol processes ( Vacheron et al., 2013 ; Bashan et al., 2014 ; Shahrajabian et al., 2023 ). More in particular, plant growth-promoting rhizobacteria (PGPR) suggest a promising solution for more productive and sustainable agriculture practices ( Chaudhary et al., 2023 ). The use of biological products in agriculture has increased substantially in the last decade.…”
Section: Introductionmentioning
confidence: 99%